Soft-Tissue Reconstruction in Progressive Hemifacial Atrophy: Current Evidence and Future Directions. Issue 3 (1st July 2022) - Abi-Rafeh, Jad; Jaberi, Mehrad; Cattelan, Leila; Aljerian, Albaraa; Gilardino, Mirko S.
Abstract : Background: Progressive hemifacial atrophy is a rare disorder characterized by gradual unilateral soft-tissue atrophy in the face, which may also include clinically significant degeneration of underlying muscle and bone. In recent years, there has been a growing body of evidence regarding different soft-tissue reconstructive strategies in progressive hemifacial atrophy and the impact of intervention timing on disease progression. This article provides a comprehensive synthesis of the latest evidence to guide optimal management. Methods: A comprehensive multidatabase search was performed through April of 2020 using relevant search terms to identify clinical studies. Outcomes, complications, and disease- and patient-related indications pertaining to different soft-tissue reconstructive strategies in progressive hemifacial atrophy were collected and critically appraised. Results: Thirty-five articles reporting on a total of 824 progressive hemifacial atrophy patients were evaluated; 503 patients (61 percent) were managed by microvascular free flaps, 302 patients (37 percent) were managed by autologous fat grafts, and 19 patients (2 percent) were managed by pedicled flaps. A detailed synthesis of outcomes is presented in this article, as is a comparative evaluation of different microvascular free flap options. Conclusions: Soft-tissue reconstruction in progressive hemifacial atrophy remains an evolving field. Operative decision-making is often multifaceted, and guided by specific volumetric, aesthetic, and functional deficiencies. Serial fat grafting is the primary modality used for patients with mild soft-tissue atrophy, whereas microvascular free flaps widely remain the treatment of choice for reconstruction of large-volume defects. There exists a growing role of graft supplementation to improve fat graft survival, whereas recent evidence demonstrates that early intervention may help curb disease progression.